Dose-dependent effect of a single GnRHa injection on the spawning of meagre (Argyrosomus regius) broodstock reared in captivity - Fernandez-Palacios, Hipolito; Schuchardt, Dominique; Roo, Javier; Izquierdo, Marisol; Hernandez-Cruz, Carmen; Duncan, Neil (Spanish Journal of Agricultural Research, 2014)
The present study aimed to determine the spawning efficacy, egg quality and quantity of captive breed meagre induced with a single gonadotrophin‐releasing hormone agonist (GnRHa) injection of 0, 1, 5, 10, 15, 20, 25, 30, 40 or 50 µg kg-1 to determine a recommended optimum dose to induce spawning. The doses 10, 15 and 20 μg kg-1 gave eggs with the highest quality (measured as: percentage of viability, floating, fertilisation and hatch) and quantity (measured as: total number of eggs, number of viable eggs, number of floating eggs, number of hatched larvae and number of larvae that reabsorbed the yolk sac). All egg quantity parameters were described by Gaussian regression analysis with R2=0.89 or R2=0.88. The Gaussian regression analysis identified that the optimal dose used was 15 μg kg-1. The regression analysis highlighted that this comprehensive study examined doses that ranged from low doses insufficient to stimulate a high spawning response (significantly lower egg quantities, p<0.05) compared to 15 μg kg-1 through to high doses that stimulated the spawning of significantly lower egg quantities and eggs with significantly lower quality (egg viability). In addition, the latency period (time from hormone application to spawning) decreased with increasing doses to give a regression (R2=0.93) which suggests that higher doses accelerated oocyte development that in turn reduced egg quality and quantity. The identification of an optimal dose for the spawning of meagre, which has high aquaculture potential, represents an important advance for the Mediterranean aquaculture industry.